Interplay between polygenic risk and family processes in predicting trajectories of adolescent externalizing behaviors - Su, Jinni; Jamil, Belal; Elam, Kit K.; Trevino, Angel D.; Lemery-Chalfant, Kathryn; Seaton, Eleanor K.; Cruz, Rick A.; Grimm, Kevin J. (Frontiers in Psychiatry, 2025)
IntroductionThere is limited understanding on how polygenic scores derived from genome-wide association studies of adult and child psychopathology may uniquely predict childhood traits. The current study took a developmental approach to examine the interplay between adult-based and child-based polygenic scores with family processes in predicting trajectories of externalizing behaviors from late childhood to early adolescence among racially-ethnically diverse youth.MethodData were drawn from the non-Hispanic White (N = 5,907), non-Hispanic Black (N = 1,694), and Hispanic youth (N = 2,117) from the adolescent brain cognitive development (ABCD) study. Parents reported on youth externalizing behaviors at baseline (T1, age 9/10), 1-year (T2, age 10/11), 2-year (T3, age 11/12), and 3-year (T4, age 12/13) follow-up assessments. Youth reported on parenting and family environment at T1 and provided saliva or blood samples for genotyping.ResultsBoth polygenic scores for adult externalizing and childhood aggression predicted greater likelihood of following trajectories with higher externalizing behaviors. Among non-Hispanic White youth, polygenic scores also predicted greater family conflict, which in turn predicted higher externalizing behavior trajectories.DiscussionOur findings indicated that both adult-based and child-based polygenic scores for externalizing behaviors are useful in predicting trajectories of externalizing behaviors, highlighting developmental continuity in genetic influences. Family processes, especially family conflict, play an important role in adolescent externalizing behaviors across racial-ethnic groups, suggesting the need to target family conflict in intervention efforts. Findings also highlight the importance of conducting research in diverse populations, including improving diversity in genetically informed studies.